Dualist heresy in Aquitaine and the Agenais, c.1000-c.1249 - Taylor, Claire (1999)
This thesis offers an account of dualist heresy in medieval Aquitaine. The first part asserts that the heresy referred to in early eleventh-century sources was dualist and originated in Balkan Bogomilism. It does this by combining two established methodologies. Through the first, reading the sources in their social context, it finds the poor experiencing increased poverty and oppression, and that some amongst the laity and clergy were observing signs prefiguring The End of historical time. Not unexpectedly, some responded through dissent and demanded reform and justice: a new system of values, in other words. Then the thesis adopts a comparative methodology in a 'global' context. It finds that the accounts of dissent do more than identify Apocalypticism or primitive communism. They make reference to dualist cosmology and practice. Dualists in the Balkans were intent on spreading their teaching world-wide, and this period saw increased contacts with the west. The spread of Bogomilism to Aquitaine was thus both likely and possible, and appears to have had some success.